2005
DOI: 10.1021/jm049530m
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of CC Chemokine Receptor-3 (CCR3) Antagonists with Picomolar Potency

Abstract: Starting with our previously described(20) class of CC chemokine receptor-3 (CCR3) antagonist, we improved the potency by replacing the phenyl linker of 1 with a cyclohexyl linker and by replacing the 4-benzylpiperidine with a 3-benzylpiperidine. The resulting compound, 32, is a potent and selective antagonist of CCR3. SAR studies showed that the 3-acetylphenyl urea of 32 could be replaced with heterocyclic ureas or heterocyclic-substituted phenyl ureas and still maintain the potency (inhibition of eotaxin-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 44 publications
(59 reference statements)
1
43
0
Order By: Relevance
“…However, these phenethyl-linked compounds showed significant affinity for other GPCRs. 56 For example, 24e was reported to bind 5HT 2A receptors with a K i value of 11 nM. Although the selectivity for CCR3 over 5HT 2A was improved in case of the benzyl-linked analogues (n 5 1, not shown), the potency was reduced simultaneously.…”
Section: E (N-ureidoalkyl)benzylpiperidines and N-arylalkylpiperidinmentioning
confidence: 95%
“…However, these phenethyl-linked compounds showed significant affinity for other GPCRs. 56 For example, 24e was reported to bind 5HT 2A receptors with a K i value of 11 nM. Although the selectivity for CCR3 over 5HT 2A was improved in case of the benzyl-linked analogues (n 5 1, not shown), the potency was reduced simultaneously.…”
Section: E (N-ureidoalkyl)benzylpiperidines and N-arylalkylpiperidinmentioning
confidence: 95%
“…This has been typical of some chemical series of our CCR3-active molecules (Delucca et al, 2005) but has not been reflected in their potencies against mouse CCR3. Compound 2 was unusual in exhibiting subnanomolar chemotaxis IC 50 against mouse CCR3, a 15-fold increase in potency over the binding number.…”
Section: Discussionmentioning
confidence: 90%
“…However, chemotaxis IC 50 were divergent. Like other compounds in the cyclohexyl series (Delucca et al, 2005), compound 1 was somewhat less potent in the chemotaxis assay than in binding; in contrast, compound 2 was 15-fold more potent in mouse chemotaxis, just as it was more potent in human chemotaxis than in human binding. When dosed p.o.…”
Section: Development and Characterization Of A Model Of Ccr3-dependenmentioning
confidence: 85%
See 1 more Smart Citation
“…Although several nonpeptide compounds that inhibit binding of CCL11 to CCR3 have been reported (Sabroe et al, 2000;White et al, 2000;Saeki et al, 2001;Wan et al, 2002, De Lucca et al, 2005, their in vivo effectiveness has not yet been demonstrated in any nonhuman primates. YM-355179 is a novel, selective, and orally available low-molecular weight CCR3 antagonist that has been chemically synthesized in our laboratories.…”
mentioning
confidence: 99%